The assessment of the fuel additive impact on moving grate boiler efficiency. Issue 6 (December 2019) - Junga, Robert; Pospolita, Janusz; Niemiec, Patrycja; Dudek, Maciej
Abstract: The purpose of the work is to determine the impact of a commercial coal additive on the efficiency and the pollutants emissions of an industrial boiler. The tests were carried out in a 41.1 MW thermal output moving grate boiler in common operating conditions for a period of two months. At that time, coal was alternately dosed with and without the additive. The amount of the additive to coal ratio was fixed at 1L/Mg during the tests. The additive applied was a 20% aqueous solution of four compounds, i.e. isopropanol, manganese (II) acetate tetrahydrate, acetic acid glacial … % and N, N-Dimethylethanolamine. The samples of coal, bottom and fly ash were collected from the installation twice a day during the tests in order to check their properties. The boiler's main energy parameters and the emission levels of CO, NOx, SO2 and dust were measured and registered. The additive influence on the boiler operation was evaluated based on the efficiency and three indicators which highlighted this impact. The additive influence was mainly demonstrated in boiler efficiency increase, in the range of 0.5–1 p.p., as well as the oxygen concentration in the flue gas which indicates that there was a decreased amount of the combustion air. On the other hand, the studies do not show any evident influence on the NOx, SO2 and CO emissions with the applied catalyst to fuel ratio. The research showed that even a little improvement of efficiency gives a measurable economic effect. Highlights: Coal additive tests were carried out in a 41.1 MW thermal output moving grate boiler. Coal, bottom and fly ash were sampled twice a day during a period of two months to assess the additive impact. The oxygen concentration in the flue gas decreased during additive dosage. The additive increased boiler efficiency in the range of 0.5–1 p.p. A little improvement of efficiency gives a measurable economic effect.